Former Yugoslav Republic of Macedonia : Staff Report for the 2003 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
This paper evaluates the 2003 Article IV Consultation and a Request for a Stand-By Arrangement (SBA) for the Former Yugoslav Republic of Macedonia (FYRM). The Article IV policy discussions focused on regaining a sustainable fiscal and external position, restarting economic growth and job creation, and addressing vulnerabilities resulting from public sector indebtedness, banking sector fragility, and euroization of bank and government balance sheets. FYRM has also requested IMF support of the program under an SBA in the amount SDR 20 million.